ANALYSIS OF THE INFLUENCE OF DIVIDEND POLICY ON STOCK VOLATILITY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Andi Izatul Fiddah; Amraeni; Nursinah Amrullah; Ririn Mardhani Syakur (CV. Radja Publika, 2026)
This study aims to examine how the dividend payout ratio and dividend yield impact stock price volatility, with inflation as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2023. Secondary data are used in this study, drawn from financial statements and annual reports. This study includes manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2023, as well as those that have held an IPO since at least 2018. Forty-four companies met the research criteria, selected using a purposive sampling method. This study used multiple regression analysis. The results show that only the dividend payout ratio significantly influences stock price volatility. Stock prices are riskier when the dividend payout ratio is more dynamic, and vice versa. The study also shows that the dividend payout ratio and dividend yield do not affect stock price volatility.